HUBUNGAN POWER OTOT TUNGKAI DAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN ACCURACY SMASH PADA TIM VOLI PUTRA HUHA JUNIOR PEKANBARU - Denni Alexander; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem of this research is the result smash it does not optimal and it does not meet the desired expectations, either. It is suspected due to low physical capabilities including leg muscle power and muscle strength of arms and shoulders. So, this research was conducted to determine whether there is correlation between power and leg muscles, arm and shoulder strength with Smash accurationin Team Volleyball Men's Junior HUHA Pekanbaru. The samples of this research was Volleyball Men's Team of JuniorHUHA Pekanbaru, the participate about 12 students. The technique to collecting of sample from total sampling. The instrument of this research was vertical power jump test, which aims to measure the power of leg muscle than expanding dynamometer test aimed of measuring the strength of the arm and shoulder’s muscles and smash accuration test which is intended to measure the smash accuracy. And then, analyzing the statistics to test normality with Lilifors test in significant 0,05α.The hypothesis suspected, there is a significant correlation between leg muscle power and strength of arms and shoulders with an smash accuracy on Team Volleyball Men's Junior HUHA Pekanbaru. Based on Lilifors analysis resulted Lcount (x1) about 0,19and Ltabel0,242, Lcount (x2) about 0,16and Ltabel0,242, Lcount(y) about 0,22 and Ltabel 0,242 so, Lcount<Ltable, which the samples come from the population of normal distribution. Then, the correlation result product moment between leg muscle power and strength of arms and shoulders with a smash accuration resulted rcount 0,629and rtable 0,602 so rcount>rtable effected Ho rejected and Ha accepted. So, there is the significant correlation between leg muscle power and strength of arms and shoulders with a smash accurationon Team Volleyball Men's Junior HUHA Pekanbaru.Keywords: power of leg muscle,strenghtof the arm and shoulder muscles, accuracy smash